Morphological spelling development - Larkin, R; Snowling, M (2008)
Treiman and Cassar (1996) argued that young children are capable of assembling spellings from their constituent morphemes. The present study aims to replicate the methodology used by Treiman and colleagues to investigate whether young children in the UK are using morphological spelling strategies. Eighty-three children between five and nine years took part in the study. The children completed a test of single word reading, alongside a spelling test consisting of 16 one-morpheme words (e.g., taste) SYS:Font ID=NCI;and 16 two-morpheme words (e.g., raced). The results provide no evidence that young children are using morphology to aid their spelling, and are discussed in relation to models of spelling development.